Validity Of Scale Organizational Violence In The Covid-19 Era - Javier Carreón Guillén; Francisco Espinoza Morales; Cruz García Lirios (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
In the context of organizations and their relationship with the increasingly competitive environment, leaders have been pressured to establish control systems in which the differences between employees are exacerbated since, in the absence of labor competencies, these are They are intended to substitute for acts of loyalty to the company that lead to violence towards those who are the culprits of poor performance or are not seen as part of a working group. This is how organizational violence is justified within collaborative teams, as would be the case of Higher Education Institutions where the phenomenon is exacerbated with the emergence of electronic technologies, devices, and networks. The objective of this study was to establish the reliability and validity of an instrument that measures organizational violence. A non-experimental, cross-sectional, and confirmatory study was carried out with a selection of 100 students from a public university in central Mexico. The results show that organizational violence would be made up of eight factors: prejudice, depersonalization, benevolence, harassment, subjugation, objectification, stigma, and harassment, which show the limits of the study and guidelines of research concerning equity.